2019
DOI: 10.1002/ajpa.23766
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial skeletal response to encephalization: How do we know what we think we know?

Abstract: Dramatic changes in cranial capacity have characterized human evolution. Important evolutionary hypotheses, such as the spatial packing hypothesis, assert that increases in relative brain size (encephalization) have caused alterations to the modern human skull, resulting in a suite of traits unique among extant primates, including a domed cranial vault, highly flexed cranial base, and retracted facial skeleton. Most prior studies have used fossil or comparative primate data to establish correlations between br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 212 publications
0
26
0
Order By: Relevance
“…Table S7). These terms have appeared prominently in the human evolution literature in the context of neoteny and delay brain maturation, brain growth and the craniofacial phenotype in between species comparisons [6,[30][31][32]. Two chromatin regulators with mSNC in regulatory regions are present in these two ontology terms and are associated to neurodevelopmental disorders: KDM6A (mSNC in promoter), which associates to the H3K4 methyltransferase complex [27], and is mutated in patients with Kabuki syndrome [33]; and PHC1 (mSNC in promoter), a component of the repressive complex PRC1 [27], found in patients with primary microcephaly-11 [18].…”
Section: Resultsmentioning
confidence: 99%
“…Table S7). These terms have appeared prominently in the human evolution literature in the context of neoteny and delay brain maturation, brain growth and the craniofacial phenotype in between species comparisons [6,[30][31][32]. Two chromatin regulators with mSNC in regulatory regions are present in these two ontology terms and are associated to neurodevelopmental disorders: KDM6A (mSNC in promoter), which associates to the H3K4 methyltransferase complex [27], and is mutated in patients with Kabuki syndrome [33]; and PHC1 (mSNC in promoter), a component of the repressive complex PRC1 [27], found in patients with primary microcephaly-11 [18].…”
Section: Resultsmentioning
confidence: 99%
“…As disturbances in the differentiation of body proportions were not taken into account, relative or absolute microcephaly/macrocephaly was not distinguished. There is a relationship between the size of the brain and the size of the skull 30 , the body size 31 , and the neurological capacity of organisms 31 . Previous studies have shown that tetraplegia is accompanied by short stature 3 , though current studies have shown that tetraplegia is accompanied by microcephaly, which confirms the theory of encephalysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to this inference, the bony labyrinth pattern common to the extant great apes may be a secondary effect of independent acquisition of large brains. Understanding the actual developmental mechanisms and processes that produce variation of craniofacial structures remains a major challenge (Lesciotto & Richtsmeier, 2019), and a better understanding of developmental interactions between the brain and labyrinth is needed.…”
Section: Living Great Apes and Miocene Apesmentioning
confidence: 99%